Pemaparan Teknologi Biometrika Dan Google Cloud Vision Api Di SMK Dwi Tunggal 2 Tanjung - Andi Marwan ElHanafi; Ruswan Nurmadi; Tommy T; Rosyidah Siregar (Jurnal TUNAS, 2020)
Biometrics technology and its combination with Cloud Computing has become a technological trend today which has been utilized in various applications and services such as social media. The low insight into this technology is still often found in the younger generation, especially in high school students. This dedication activity is carried out at SMK Dwi Tunggal 2 Tanjung with class X students. This dedication aims to provide insights and knowledge of Biometrika technology and Google Cloud Vision API which are widely used by various Google services in the hope that this activity can be useful to educate generations especially in the fields of Biometrics and Cloud Vision technology.